Biogenesis and function of circular RNAs and their implications in the Down syndrome brain - Zainal Abidin, Shahidee; Razali, Nurul Nadirah; Cheah, Pike-See; Ling, King-Hwa (Frontiers in Genetics, 2025)
Circular RNAs (circRNAs), a class of covalently closed, non-coding RNAs, have recently emerged as crucial regulators of gene expression. They exert their roles through microRNA (miRNA) sponging, transcriptional regulation, and interactions with RNA-binding proteins (RBPs). Increasing evidence suggests that circRNAs play important roles in neurodevelopmental disorders, including Down syndrome (DS). DS is a condition caused by trisomy of chromosome 21 and characterised by intellectual disability (ID), neuroinflammation, and increased risk of early-onset Alzheimer’s disease (AD). Aberrant circRNA expression in DS may contribute to pathogenesis by disrupting competing endogenous RNA (ceRNA) networks, modulating synaptic plasticity, and influencing key molecular pathways, including EZH2-mediated chromatin remodelling, immune response regulation, and neuronal differentiation. Despite these emerging insights, the role of circRNAs in DS remains largely underexplored compared to their well-recognised functions in cancer and other neurological disorders. Most current studies have focused on transcriptomic analyses, identifying differentially expressed circRNAs and predicting their interactions with miRNAs and mRNAs. However, these findings require further experimental validation to uncover the precise mechanisms through which circRNAs contribute to DS pathophysiology. This review highlights the association of circRNAs with DS, emphasising their dysregulation and mechanistic interactions with miRNAs and mRNAs. It further explores how these circRNA-mediated mechanisms may contribute to intellectual disability and impaired neurodevelopment, based on current evidence.